2015
DOI: 10.1063/1.4932648
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence-induced jumping of nanoscale droplets on super-hydrophobic surfaces

Abstract: The coalescence-induced jumping of tens of microns size droplets on super-hydrophobic surfaces has been observed in both experiments and simulations. However, whether the coalescence-induced jumping would occur for smaller, particularly nanoscale droplets, is an open question. Using molecular dynamics simulations, we demonstrate that in spite of the large internal viscous dissipation, coalescence of two nanoscale droplets on a super-hydrophobic surface can result in a jumping of the coalesced droplet from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(99 citation statements)
references
References 22 publications
4
94
0
1
Order By: Relevance
“…58 However, experimental and numerical studies have demonstrated that the coalescence of smaller droplets (<10 μm, even down to nanometer size) could cause the droplets to jump away from the surfaces. 4,3335 Recent studies have provided strong evidence that viscous dissipation is not important at length scales larger than 1 μm. 4,35,36 Instead, finite surface adhesion and unequal momentum flow in the vertical direction govern and limit the droplet jumping.…”
Section: Resultsmentioning
confidence: 99%
“…58 However, experimental and numerical studies have demonstrated that the coalescence of smaller droplets (<10 μm, even down to nanometer size) could cause the droplets to jump away from the surfaces. 4,3335 Recent studies have provided strong evidence that viscous dissipation is not important at length scales larger than 1 μm. 4,35,36 Instead, finite surface adhesion and unequal momentum flow in the vertical direction govern and limit the droplet jumping.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the method of distinguishing the phase based on potential energy has a lower computational cost than the density criterion and avoids the undesirable dependency on the size of the subdomain needed for density calculation. It has also been successfully used in study of coalescence of nanoscale droplets on a solid surface [40]. After 2,000 ps, the system reaches a steady state and a spherical-shaped liquid Ar droplet is formed in the center of the simulation box.…”
Section: B the MD Modelmentioning
confidence: 99%
“…In recent years, coalescence-induced droplet jumping on a superhydrophobic surface has received more and more attention [1][2][3][4][5][6][7][8][9][10][11], because it has been applied to various fields, including condensation heat transfer [12,13], self-cleaning [14], anti-icing [15,16], anti-dew [17] and so forth. However, the jumping velocity affects the efficiency of these applications.…”
Section: Introductionmentioning
confidence: 99%